Shibori Teknik Kacak Three Colors pada Penciptaan Ready to Wear Deluxe - Kemala, Alya Bela; Suharno, Suharno; Marlianti, Mira (Jurnal Pendidikan dan Penciptaan Seni, 2025)
The kacak technique is one of the techniques in making shibori. This technique is generally only used to produce shibori with one color. This is the basis for the creation of this work, namely, to produce three colors in shibori fabric with the kacak technique. Therefore, the purpose of creating this work is to find a new application of the kacak technique in shibori. The results of this finding are then used as the main material in the creation of ready-to-wear deluxe, which is combined with an angklung motif stamp batik as a complement. To realize this work, the creation method used is the three-stage design process, including problem definition and research, creative exploration, and implementation. The results of this creation are in the form of 4 (four) ready-to-wear deluxe looks presented at the Indonesia International Modest Fashion Festival (IN2MF) 2024 at the Jakarta Convention Center (JCC).